(untitled) (REVISTA NODO, 2019)
Which is the criterion that serves to save from time and human action certain areas of a city that are worthy of the title of “historical”? What is the function of the delimitation of entire neighborhoods that are promoted as “interesting” and that deserve to be rescued from processes of decrepitude or marginalization and need to be elevated to the status of singular places, whose value translates into armoring with respect to any factor that alters or jeopardize its calmness? We will spot on the consequences, in the form of gentrification or emptying, of the production of patrimonialized centers in Latin American cities, dynamics whose paradoxical effect is always the one which attempts to expel them from history, that is, from conflict and uncertainty.